Analysis of Income Inequality in ASEAN Countries - Anasta, Akila; Sylviana, Widya (Jurnal Ilmu Ekonomi Terapan, 2024)
This study aims to analyze income inequality in ASEAN countries. The variables in this study are income inequality as the dependent variable, FDI, GDP per capita, personal remittances, and economic openness as independent variables. The scope of this research is ASEAN countries from 2009 to 2021. This research uses panel data regression method. The estimation results in this study show that FDI and GDP per capita variables significantly affect income inequality in ASEAN. Meanwhile, personal remittance and economic openness have no significant effect.